2014
DOI: 10.5812/ircmj.14119
|View full text |Cite
|
Sign up to set email alerts
|

The Voluntary Response Index in Electromyographic Study During Landing Test of the Patients With ACL Deficiency: A New Study Protocol

Abstract: Background:Daily Increased rate of anterior cruciate ligament (ACL) injuries in athletes calls for more investigation in these patients to differentiate copers from noncoper ACL-deficient (ACLD) knees as soon as possible.Objectives:The current study aims to introduce a new electromyographic protocol, named voluntary response index (VRI), that might help to categorize and differentiate patients with ACLD knee from others in the early stage.Materials and Methods:Thirty-four patients with ACLD knee were allocated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The VRI of sEMG data had also been used to examine changes in the movement pattern of the cervical muscle groups during head reposition in young adults with chronic neck pain, and it was found that patients with chronic neck pain exhibited altered EMG patterns during voluntary sagittal neck motions [11]. The examples from these studies and several others indicated that VRI analysis could show changes in the CNS motor output that occurred with rehabilitative interventions or disorder progression [9,[11][12][13]17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The VRI of sEMG data had also been used to examine changes in the movement pattern of the cervical muscle groups during head reposition in young adults with chronic neck pain, and it was found that patients with chronic neck pain exhibited altered EMG patterns during voluntary sagittal neck motions [11]. The examples from these studies and several others indicated that VRI analysis could show changes in the CNS motor output that occurred with rehabilitative interventions or disorder progression [9,[11][12][13]17].…”
Section: Discussionmentioning
confidence: 99%
“…Instead of examining individual muscle activity, it would be more beneficial to examine the activation pattern of all muscles engaged in the entire prototype of a task. In practical application, the magnitude and the similarity activities of all muscles engaged in voluntary movement are studied as a whole rather than studying each muscle individually [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the scarcity of evidence regarding the effects of proprioception training on VRI components in athletes with ACLR, especially in the aquatic environment, it was difficult to make a direct comparison with previous studies. However, many studies have investigated CNS motor output changes during the progression of certain disorders (13,(21)(22)(23)(24). For example, Cheng et al conducted a study to investigate cervical EMG responses during head tasks in patients with neck pain.…”
Section: Similarity Indexmentioning
confidence: 99%
“…Voluntary response index methodologies have been applied in diverse research areas, including incomplete spinal cord injuries (17,18), shoulder dysfunction (19), trunk muscle fatigue (20), anterior cruciate ligament (ACL) injury (21), and trunk muscle activity during variable weight lifting (22). A higher SI value indicates superior motor control in voluntary tasks.…”
Section: Introductionmentioning
confidence: 99%